Transportation of Pollutants of the Danube River into the (Western) Black Sea - Muftuoglu, A.E. (Asian Journal of Chemistry, 2013)
At 14 stations on the Western Black Sea shelf, water and sediment samples were collected from the water column and the sea-bed during August 2003 and June 2004. The metals content (Al, Fe, Mn, Pb, Cu, Zn, Ni, Cd, Cr and Hg) of these samples was investigated to determine the influence and transportation of metal pollutants in the Danube River on the Western Black Sea. Pb, Cd, Hg and Cr concentration in the sediment was above the shale average (20, 0.2, 300 and 100 μg g-1 respectively) while Fe, Cu, Zn including Ni concentration was determined to be below the shale average (4.7 %, 50, 90 and 80 μg g-1 respectively). High total organic carbon (TOC, 2.5-4.11 %) and dissolved hydrogen sulfur (DHS, 249-419 μg g-1) observed, suggested widespread pollution, cause by carry-over water and suspended solids in the Danube River. Additionally, the high concentration of Pb, Cd and Hg, in the surface sediment indicated that anthropogenic input is a major contributor of pollution via the Danube River.